Review on Acute Cardio-Cerebral Infarction: a Case Report - Cotelli, Maria Sofia; Manelli, Filippo (Faculty of Medicine Universitas Padjadjaran, 2021)
Objective: To present a case of relapsed spinal cord infarction (SCI) as an acute spinal emergency in an in-patient elderly male patient. Methods: This report presents a case of an in-patient 84 years-old man who was admitted due to acute paraparesis with urge incontinence and sudden worsening after initial improvement. To assess his condition, spine magnetic resonance was performedResults: The spine magnetic resonance confirmed relapse of spinal cord infarction, which also involved the medullar conus.Conclusion: This case report presents a very rare event that is poorly described in literature. A strict follow up of risk factors and regular neurological evaluations during ihospitalization are recommended, especially in older patients.